Cancer rate of Bethesda category II thyroid nodules - Francesk Mulita; Fotios Iliopoulos; Christos Tsilivigkos; Levan Tchabashvili; Elias Liolis; Charalampos Kaplanis; Ioannis Perdikaris; Ioannis Maroulis (Medicinski glasnik, 2021)
Aim: Thyroid nodules are very common and may be found in more than 50% of the population. Fine-needle aspiration cytology (FNAC) of thyroid nodules is a very useful diagnostic tool with high sensitivity and predictive value for diagnosis. The Bethesda System for Reporting Thyroid Cytopathology (BSRTC) uses six categories for thyroid cytology reporting (I-nondiagnostic, IIbenign, III-atypia of undetermined significance (AUS)/ follicular lesion of undetermined significance (FLUS), IV-follicular neoplasm/suspicious for follicular neoplasm (SFN), V-suspicious for malignancy, and VI-malignant. Our objective was to determine the malignancy rate in Bethesda II nodules. Methods: From June 2010 to May 2020 a retrospective analysis was performed among 1166 patients who underwent thyroid surgery for benign thyroid diseases in our institution. Thyroid cytopathological slides and Ultrasound (US) reports were reviewed and classified according to the BSRTC. Data collected included age, gender, cytological features, and histological type of thyroid cancer. Results: During the study period, 44.77% (522/1166) of patients with an FNA categorized as Bethesda II underwent thyroid surgery. Incidental malignancy was found in 1.53% (8/522) cases of Bethesda II. The most common malignant tumour type was papillary thyroid carcinoma. Conclusion: The current study demonstrates that incidental thyroid carcinoma can be diagnosed after thyroidectomy even in patients with an FNA categorized as Bethesda II.
Keywords: benign nodule; Bethesda classification; malignancy rate